Adherence to Antihypertensive Drugs Assessed by Hyphenated High‐Resolution Mass Spectrometry Analysis of Oral Fluids. Issue 14 (21st July 2020) - Lauder, Lucas; Ewen, Sebastian; Kunz, Michael; Richter, Lilian H. J.; Jacobs, Cathy M.; Kindermann, Ingrid; Böhm, Michael; Meyer, Markus R.; Mahfoud, Felix
Abstract : Background: It is currently unknown if antihypertensive drugs can be monitored in oral fluid (OF) using liquid chromatography coupled to high‐resolution mass spectrometry. Methods and Results: We assessed adherence using liquid chromatography coupled to high‐resolution mass spectrometry in OF, plasma, and urine of 56 consecutive patients with hypertension referred to a tertiary hypertension unit. Of these patients, 59% were completely adherent (all drugs detectable in urine), whereas 29% and 13% were partially adherent (1 drug not detectable in urine) or nonadherent (>1 drug not detectable in urine), respectively. Adherent patients were on fewer antihypertensive drugs ( P =0.001), had fewer daily drug doses ( P =0.012), and had lower 24‐hour ambulatory systolic ( P =0.012) and diastolic ( P =0.009) blood pressures than nonadherent or partially adherent patients. Most drugs were detected in urine compared with plasma and OF (181 versus 119 versus 88; P =0.001). Compared with urine and plasma, detection rates of angiotensin‐converting enzyme inhibitors, angiotensin II receptor blockers, and diuretics were lower in OF. There was no difference in the frequency of detecting β blockers ( P =1.0) and calcium channel blockers ( P =0.063) when comparing OF with urine. There was no difference in the number of calcium channel blockers ( P =0.727), β blockers ( P =1.000), thiazide diuretics ( P =0.125), and α‐2 agonists ( P =0.125) identified between OF and plasma. Conclusions: This study shows the feasibility of drug adherence testing for several antihypertensive drugs, especially those without acidic components, in OF, with a similar recovery compared with plasma. Therefore, drug adherence testing in OF should be further explored as a noninvasive approach, which can easily be performed in an "out‐of‐office" setting.